CHARACTERIZATION OF BIOSURFACTANT PRODUCED BY PSEUDOMONAS AERUGINOSA EXPOSED TO CADMIUM AND COPPER - Tan, Weng Liang (2018)
Cadmium and copper are extensively used in different industrial sectors before being discharged as industrial effluent and causing pollution towards the environment and increases the health risk when being uptake by humans. The aims of this study were to evaluate the effect of Cd and Cu to induce production of biosurfactants and to characterize the biosurfactant produced using Fourier-Transform Infrared Spectroscope (FTIR). Results from the study showed that P. aeruginosa was able to tolerate Cu and Cd up to 2.0 mg/L and 0.1 mg/L respectively, which both concentration were 10x higher than the permissible limit allowed by the Environmental Quality Act (Industrial Effluent) Regulation, according to the Department of Environment, Malaysia. Recovery of biosurfactant from P. aeruginosa exposed to Cu and Cd were 0.051 g/g of bacterial cells and 0.125 g/g of bacterial cells, respectively. FTIR analysis obtained from control biosurfactant sample without metals induction, and biosurfactant samples induced with Cu and Cd, respectively showed major peaks at 3276 and 1351 cm-1 suggesting the presence of protein and lipid. This suggests that the type of biosurfactant produced by P. aeruginosa was lipoprotein in the presence of Cu or Cd, as in the normal condition without metal induction